COMPARISON OF INTEGRATED DIGITAL MARKETING TO ENHANCE THE BRAND RECOGNITION BETWEEN SOUVENIR BUSINESSES AND ITS CUSTOMER - Lestari, Janiva Ayu; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: In business, there are offline marketing and online marketing/digital marketing, the constant debate around choosing the better between offline and online marketing, people forget the real deal-looking for the best of both world, and businesses must to have strategy to compete each other especially with their brand recognition. However, commonly businesses do not have consistency to recognize the brand/promoting with digital media. In Manado, which is still very lacking in applying digital marketing to embed the brand of customer mind and this research talk about souvenir businesses in Manado. This research is qualitative research and the data collected by in-depth interview, there are 3 souvenir businesses (Merciful Building, Miens Souvenir Manado and Bahaga Kaos Manado) and 10 customers. Merciful Building applied 70% offline and 30% ofnline. Miens Souvenir Manado and Bahaga Kaos Manado 50% offline and 50% online. The result has gotten from in-depth interview are 50% informant know the store through offline first after that they know their social media and 50% informant know the store through online (digital marketing). So, they managed to deliver messages or recognize brand of digital marketing. Proven by matching the results of what souvenir businesses have conveyed with what customers get.Â Keywords: digital marketing, brand recognition